Improved Isolation of Anaerobic Bacteria From the Gingival Crevice Area of Man - Gordon, D. F. (1971)
A roll tube technique (Hungate method) was employed in an attempt to cultivate a maximal portion of the organisms in the gingival crevice area of man. This technique achieves an anaerobic state by flushing the local environment with oxygen-free gas. Once collected, the crevicular debris was immediately placed into sterile oxygen-free test tubes which were flushed out by the oxygen-free gas. In this manner, the samples were weighed, dispersed, diluted, and cultured in roll tubes and plates. The medium for control (Brewer Jar technique) and Hungate techniques was Heart Infusion Agar fortified with 10% defibrinated horse blood. When the Hungate technique was used, the recovery of viable bacteria, as a percentage of the direct microscopic count, was significantly greater than plates incubated aerobically or utilizing the Brewer Anaerobic technique. Cultural counts by using the Hungate method averaged 41.3% for six samples when 90% nitrogen and 10% hydrogen were used, 70.4% for eight samples when 85% nitrogen, 10% hydrogen, and 5% carbon dioxide were used, and 63.4% for eight samples when 100% carbon dioxide was the gaseous atmosphere. At no time were cultural counts, by using anaerobic plates (Brewer Jar), more than 24% of the direct microscopic count. This suggests that exclusion of oxygen and the presence of carbon dioxide maximized recovery of gingival crevice bacteria.